Achieving significantly enhanced visible-light photocatalytic efficiency using a polyelectrolyte: the composites of exfoliated titania nanosheets, graphene, and poly(diallyl-dimethyl-ammonium chloride). Issue 33 (3rd August 2015) - Zhang, Qian; An, Qi; Luan, Xinglong; Huang, Hongwei; Li, Xiaowei; Meng, Zilin; Tong, Wangshu; Chen, Xiaodong; Chu, Paul K.; Zhang, Yihe
Abstract : Using a polyelectrolyte and rGO to boost the photocatalystic performance of titania nanosheet. Abstract : A high-performance visible-light-active photocatalyst is prepared using the polyelectrolyte/exfoliated titania nanosheet/graphene oxide (GO) precursor by flocculation followed by calcination. The polyelectrolyte poly(diallyl-dimethyl-ammonium chloride) serves not only as an effective binder to precipitate GO and titania nanosheets, but also boosts the overall performance of the catalyst significantly. Unlike most titania nanosheet-based catalysts reported in the literature, the composite absorbs light in the UV-Vis-NIR range. Its decomposition rate of methylene blue is 98% under visible light. This novel strategy of using a polymer to enhance the catalytic performance of titania nanosheet-based catalysts affords immense potential in designing and fabricating next-generation photocatalysts with high efficiency.